Hydrocarbon seepage and its sources at mud volcanoes of the Kumano forearc basin, Nankai Trough subduction zone. (4th June 2014) - Pape, Thomas; Geprägs, Patrizia; Hammerschmidt, Sebastian; Wintersteller, Paul; Wei, Jiangong; Fleischmann, Timo; Bohrmann, Gerhard; Kopf, Achim J.
Abstract Twelve submarine mud volcanoes (MV) in the Kumano forearc basin within the Nankai Trough subduction zone were investigated for hydrocarbon origins and fluid dynamics. Gas hydrates diagnostic for methane concentrations exceeding solubilities were recovered from MVs 2, 4, 5, and 10. Molecular ratios (C1/C2 < 250) and stable carbon isotopic compositions (δ13C‐CH4 >−40‰ V‐PDB) indicate that hydrate‐bound hydrocarbons (HCs) at MVs 2, 4, and 10 are derived from thermal cracking of organic matter. Considering thermal gradients at the nearby IODP Sites C0009 and C0002, the likely formation depth of such HCs ranges between 2300 and 4300 m below seafloor (mbsf). With respect to basin sediment thickness and the minimum distance to the top of the plate boundary thrust we propose that the majority of HCs fueling the MVs is derived from sediments of the Cretaceous to Tertiary Shimanto belt below Pliocene/Pleistocene to recent basin sediments. Considering their sizes and appearances hydrates are suggested to be relicts of higher MV activity in the past, although the sporadic presence of vesicomyid clams at MV 2 showed that fluid migration is sufficient to nourish chemosynthesis‐based organisms in places. Distributions of dissolved methane at MVs 3, 4, 5, and 8 pointed at fluid supply through one or few MV conduits and effective methane oxidation in the immediate subsurface. The aged nature of the hydrates suggests that the major portion of methane immediately below the top of the methane‐containing sediment interval is fueled by current hydrate dissolution rather than active migration from greater depth.